The eastern Churchill Province, Torngat and New Québec orogens: An overview - Wardle, Richard; Ryan, Bruce; Ermanovics, Ingo (Geoscience Canada, 1990)
Summary The eastern Churchill Province, which separates the Archean cratons of the Superior and Nain provinces in the eastern Canadian Shield, is a rare example of a two-sided EarlyProterozoic orogenic belt. The interior of the eastern Churchill Province is composed largely of reworked Archean rocks, which appear to form an extension of the Rae Province, sutured against the adjoining Superior and Nain provinces by the New Québec and Torngat orogens. Both orogens contain continental margin sequences that record the transition from initial rift to fore deep environments. Deformation was predominantly of transpressional character and was controlled by oblique convergence of the Superior and Nain cratons on the Rae Province. The New Québec and Torngat orogens have a mirror-image symmetry defined by outward-verging fold and thrust belts associated with dextral (west) and sinistral (east) transcurrent shear on their interior margins. The dominant feature of the New Québec Orogen isits broad fold and thrust belt which is developed in low- to medium-grade rocks and is analogous to the foreland zones of Phanerozoic orogens. The Torngat Orogen, however, is dominated by an extensive sinistral shear system, developed in granulite-facies crust, that provides an excellent lower crustal analogue for modern crustal-scale transcurrent fault systems.